Effects of prebiotics on the gut microbiota in vitro associated with functional diarrhea in children - Du, Zhi; Li, Jiabin; Li, Wei; Fu, Hao; Ding, Jieying; Ren, Guofei; Zhou, Linying; Pi, Xionge; Ye, Xiaoli (Frontiers in Microbiology, 2023)
Diarrhea is among the top five causes of morbidity and mortality in children. Dysbiosis of the gut microbiota is considered the most important risk factor for diarrhea. Prebiotics have shown efficacy in treating diarrhea by regulating the balance of the gut microbiota in vivo. In this study, we used an in vitro fermentation system to prevent the interference of host-gut microbe interactions during in vivo examination and investigated the effect of fructo-oligosaccharides (FOS) on gut microbiota composition and metabolism in 39 pediatric patients with functional diarrhea. 16S rRNA sequencing revealed that FOS significantly improved αand β-diversity in volunteers with pediatric diarrhea (p < 0.05). This improvement manifested as a significant increase (LDA > 2, p < 0.05) in probiotic bacteria (e.g., Bifidobacterium) and a significant inhibition (LDA > 2, p < 0.05) of harmful bacteria (e.g., Escherichia-Shigella). Notably, the analysis of bacterial metabolites after FOS treatment showed that the decrease in isobutyric acid, isovaleric acid, NH3, and H2S levels was positively correlated with the relative abundance of Lachnoclostridium. This decrease also showed the greatest negative correlation with the abundance of Streptococcus. Random forest analysis and ROC curve validation demonstrated that gut microbiota composition and metabolites were distinct between the This is a provisional file, not the final typeset article FOS treatment and control groups (area under the curve [AUC] > 0.8). Functional prediction using PICRUSt 2 revealed that the FOS-induced alteration of gut microbiota was most likely mediated by effects on starch and sucrose metabolism. This study is the first to evince that FOS can modulate gut microbial disorders in children with functional diarrhea. Our findings provide a framework for the application of FOS to alleviate functional diarrhea in children and reduce the use of antibiotics for managing functional diarrhea-induced disturbances in the gut microbiota.